Analysis of waiting time perception of bus passengers provided with mobile service. (March 2021) - Wang, Po-Chieh; Hsu, Yu-Ting; Hsu, Chia-Wei
Highlights: Travel-irrelevant mobile service affects how bus passengers perceive waiting time. Smartphone usage is frequently associated with longer waiting time. Unexpected longer waiting time may further increase the perceived waiting time. Bus passengers show heterogeneous responses to travel-irrelevant mobile service. Young passengers are more likely to benefit from travel-irrelevant mobile service. Abstract: Smartphones and relevant mobile service have greatly influenced people's daily lives, and intense smartphone users can be commonly seen at transit stops/stations, playing with their smartphones while waiting for buses/trains. This research presents a holistic perspective for analyzing the effects of smartphone usage on transit passengers, which also considers the effects at a psychological level. Such effects may be manifested as the reduction of perceived waiting time at stops/stations against the negative emotionality induced by long waiting, such as boredom and tediousness, so as to result in improved travel experience. An on-site survey is designed and implemented over the bus system in Taipei, Taiwan, to collect the revealed responses of bus passengers in regard to waiting time perception and smartphone usage, particularly for travel-irrelevant mobile service. The survey data are modeled and analyzed in both numerical and verbal representation of perceived waiting time by using a multiple linear regression model and a cumulative proportional odds logistic model, respectively. A finite mixture model is further employed to investigate the potential heterogeneity of waiting time perception related to using smartphones for travel-irrelevant mobile service. The analysis results highlight that travel-irrelevant smartphone usage may lead to the reduction of perceived waiting, and the effect can be more significant for young passengers and those without receiving bus arrival information, especially when waiting time is prolonged. Such findings can contribute to the comprehensive consideration of passenger behavior in transit system planning and associated information/service provision strategies.